FOSTERING LANGUAGE LEARNER AUTONOMY: INDONESIAN EFL LECTURERS VOICES - Endang Darsih (English Review: Journal of English Education, 2018)
Studies reported that education in Indonesia has not been promoting learner autonomy as the main goal of the learning process. In fact, it could be one of the solutions to improve the quality of Indonesian students and a key goal for tertiary English learning. This explorative study was conducted to find out lecturer’s beliefs about learner autonomy and the activities done by the lecturers to foster learner autonomy. Seventeen lecturers from English Education Study Program were voluntarily investigated and interviewed. Questionnaires about Teachers' Beliefs about Learner Autonomy compiled by Borg and Al-Busaidi (2012) were also employed in this study. The study revealed that majority of students were assessed to be not autonomous yet and there were various efforts and activities done by the lecturers to improve learner autonomy, such as providing a project based assignment, recommending a specific web and English mobile applications to assist their learning, keep motivating the students, fostering reading habit, involving students to select materials, and applying various teaching methodology.Keywords: learner autonomy; teacher’s beliefs; fostering learner autonomy; EFL; tertiary education.